What Becomes Nature? The role of Posthumanism in Creating new Relationships between Humans and the Environment - Brylska, Aleksandra (Sensus Historiae, 2020)
In the article, the author asks a question about how the humanities – and in particular posthumanism – in combination with the natural sciences, can help in developing a new approach toward the environment. On the example of the analysis of the Chernobyl zone in Ukraine, the author proposes to look at the cultural perception of new ecosystems arising in areas affected by nuclear contamination. Because it is difficult to incorporate them into a cultural narrative of an unpolluted nature, they are not to a large extent included in (post) humanistic reflection. However, they can be one of the best examples of how, the non-human world, despite radioactive radiation, develop in places abandoned by humans. Post-nuclear spaces begin to occupy the same paradoxical position of both “degraded” and “pristine.” Their unclear biological and cultural status allows reflection on what nature is, a valuable environment and what we consider worth protecting. Reflection is very necessary to be able to develop new models of human and natural coexistence.